2017
DOI: 10.1021/acs.est.7b01589
|View full text |Cite
|
Sign up to set email alerts
|

Distribution System Operational Deficiencies Coincide with Reported Legionnaires’ Disease Clusters in Flint, Michigan

Abstract: We hypothesize that the increase in reported Legionnaires' disease from June 2014 to November 2015 in Genesee County, MI (where Flint is located) was directly linked to the switch to corrosive Flint River water from noncorrosive Detroit water from April 2014 to October 2015. To address the lack of epidemiological data linking the drinking water supplies to disease incidence, we gathered physiochemical and biological water quality data from 2010 to 2016 to evaluate characteristics of the Flint River water that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 32 publications
7
77
0
Order By: Relevance
“…No L. pneumophila was detected in small buildings, including single-family residences, in Flint in August 2015. Therefore, if the Flint water switch created more favorable conditions for L. pneumophila to grow in connected water systems (Schwake et al 2016;Rhoads et al 2017), the local conditions of the building water system and water use probably determined whether it could lead to an outbreak. Hence, key to LD outbreak prevention is proper design, operation, and maintenance of specific water systems in buildings.…”
Section: Aerosolmentioning
confidence: 99%
See 1 more Smart Citation
“…No L. pneumophila was detected in small buildings, including single-family residences, in Flint in August 2015. Therefore, if the Flint water switch created more favorable conditions for L. pneumophila to grow in connected water systems (Schwake et al 2016;Rhoads et al 2017), the local conditions of the building water system and water use probably determined whether it could lead to an outbreak. Hence, key to LD outbreak prevention is proper design, operation, and maintenance of specific water systems in buildings.…”
Section: Aerosolmentioning
confidence: 99%
“…The Michigan Department of Health and Human Services (MDHHS) reported an outbreak of LD in Genesee County in 2014 and 2015 and associated the majority of cases with one hospital in Genesee County (MDHHS 2018). Tap water surveys conducted by academic researchers showed L. pneumophila DNA markers were detectable in Flint hospital plumbing in October 2015 but not in Flint homes and small buildings in August 2015 (Schwake et al 2016;Rhoads et al 2017). However, a modeling study (Zahran et al 2018) suggested the outbreak was caused by system-wide proliferation of L. pneumophila in the potable water supply of the City of Flint, enabled by low chlorine levels in the distribution network after the switch to Flint River water as the source.…”
Section: Introductionmentioning
confidence: 99%
“…In large buildings and residential drinking water supplied by municipal water systems, detection of Legionella spp. and Legionella pneumophila has been positively associated with warm water temperatures (Borella et al 2004;Lasheras et al 2006;Raki c et al 2012;Rhoads et al 2017), water hardness (Lasheras et al 2006), inorganic contaminants (Borella et al 2004;Raki c et al 2012;Rhoads et al 2017) and water heater type (Alary and Joly 1991;Borella et al 2004) and negatively associated with disinfectant residuals (Borella et al 2004;Rhoads et al 2017). The extent to which these factors are also associated with Legionella proliferation in home plumbing served by private wells is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The water also disrupted the biofilm that forms on the inner surface of pipes, liberating the bacteria that grow there. Combined with persistently low chlorine levels in parts of the water system and the abundance of iron rust offering a ready microbial food supply, this created a situation conducive to bacterial growth (Byrne et al, ; Rhoads et al, ; Schwake, Garner, Strom, Pruden, & Edwards, ; Zahran et al, ). Efforts to counteract bacterial threats led in some instances to overchlorination, resulting in elevated levels of carcinogenic trihalomethanes (THMs) created through the interaction of chlorine and organic matter.…”
Section: Causes Of the Flint Water Crisismentioning
confidence: 99%